Case report: Allogeneic stem cell transplantation for type B insulin resistance - Ebert, Thomas; Behre, Gerhard; Weidhase, Lorenz; Vucinic, Vladan; Gewert, Cornelia; Semple, Robert K.; Stumvoll, Michael; Tönjes, Anke (Frontiers in Medicine, 2023)
Type B insulin resistance (TBIR) is a rare, often fulminant form of insulin resistance caused by autoantibodies against the insulin receptor. Untreated, its mortality is high. Various immunosuppressive regimens have shown efficacy, but treatment effects are variable and timedelayed, and drug-induced complications may arise. We report a patient with TBIR arising as a complication of Wiskott-Aldrich syndrome. Stable remission of TBIR was achieved through allogeneic peripheral blood stem cell transplantation (PBSCT) over a follow-up period of more than 1.5 years. We thus demonstrate that PBSCT can be considered a treatment option in TBIR where conventional immunosuppressive therapy is ineffective or contraindicated.